(untitled) (Oxford, 1999)
The book features a clear, comprehensive, yet manageable language syllabus, a discovery approach to the presentation of language, motivating texts from a variety of authentic sources, strong skills development with an emphasis on functional English, systematic vocabulary work recycled within the unit, a pronunciation syllabus introducing sounds, stress and intonation, optional Extension sections at the end of each unit. The Student's Book contains a detailed Grammar reference section, a Reflecting on learning section, tapescripts wordlist, and an IPA chart and irregular verb table
Keywords: English language; Textbooks for foreign speakers